Peer education as a method in sexual, reproductive health promotion and risk communication for adolescent - Rini Harianti; Tarbiyah Nurjanah; Nofri Hasrianto (Jurnal Kajian Komunikasi, 2021)
Adolescence is a period of accelerated physical, psychological, and intellectual growth and development. It includes the development in sexual maturity of adolescents. In order to promote safe and healthy sexual and reproductive health, adolescents should be equipped with adequate knowledge, attitudes, and self-efficacy regarding the matter. The role of peer influence is highest during this stgae; thus, health promotion and risk communication through peer education has shown to be effective in many settings on adolescents. The study aimed to determine the effectiveness of the peer education method as a form of health promotion in adolescent sexual and reproductive health and risk communication at SMKN “X” Pekanbaru. It was a quasi-experimental study involving 52 students. The participants were randomized into two groups, 26 in the experimental group and 26 in the control group. Data were collected using a questionnaire and analyzed by t-test. The results showed there were significant differences in the mean changes in knowledge (p=0.000), attitudes (p=0.000), and self-efficacy (p=0.000) about sexual behavior in the experimental group receiving peer education compared to the control group. However, there was no significant difference in the mean changes in the role of peer influence between the two groups (p = 0.725). Therefore, peer education as a method in sexual and reproductive health promotion and risk communication positively changed adolescents’ knowledge, attitudes, and self-efficacy about sexual behavior. Hence, it is suggested for schools to provide health promotion program regarding adolescents’ sexual and reproductive health in collaboration with the Pekanbaru City Health Office and supplement it with a peer education method.